The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1.5007458
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mononuclear cell implantation in myocardial laser channels in the ischemic heart disease surgery. Long-term results

Abstract: Abstract. Background: The problem of incomplete myocardial revascularization for diffuse and distal lesions of the myocardium is still relevant. We assessed the clinical and instrumental long-term results of autologous bone marrow cell (BMC) implantation in laser channels in ischemic heart disease with diffuse and distal coronary disease. 35 coronary heart disease (CHD) patients with diffuse and distal coronary disease during coronary artery bypass grafting (CABG) underwent BMC implantation in laser channels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…First results of this study was reported in Proceedings of the XXV Conference on High-Energy Processes in Condensed Matter (HEPCM 2017): Dedicated to the 60th anniversary of the Khristianovich Institute of Theoretical and Applied Mechanics Siberian branch of Russian Academy of Sciences (5-9 June 2017, Novosibirsk, Russia) [16].…”
mentioning
confidence: 99%
“…First results of this study was reported in Proceedings of the XXV Conference on High-Energy Processes in Condensed Matter (HEPCM 2017): Dedicated to the 60th anniversary of the Khristianovich Institute of Theoretical and Applied Mechanics Siberian branch of Russian Academy of Sciences (5-9 June 2017, Novosibirsk, Russia) [16].…”
mentioning
confidence: 99%